Free vibration and buckling analysis of thin-walled cylinders by finite element analysis - Boo, Wilson Wee Siang (2015)
This final year project deals with the free vibration and buckling analysis of two distinct types of cylindrical structure, namely the Single Thin-Walled Cylinder and the Compound Cylinder. By utilizing the commercial finite element analysis software, ANSYS, the analysis for each type of cylinder is conducted by varying certain parameters in order to isolate the free vibration and buckling behavior of the cylinders. The main parameter that is varied for both types of cylinder is the pressure applied on the cylinders. Using the Single Thin-Walled Cylinder, the simulation is repeated with different mesh densities at pressure value of zero, so as to find the optimal mesh density for conducting the simulation such that there is no wastage of computing resources. Subsequent simulations with the single and compound cylinders are conducted using the optimal mesh. For the free vibration analysis of the cylinders, Using the pressure values are varied from atmospheric pressure of 100 kPa (or 105 Pa) to 108 Pa, regardless of the area of application of the pressure, the interference values are varied (for compound cylinders), the frictional coefficient values are varied from 0 to 0.65 (for compound cylinders), and the resonant frequencies and mode shapes of vibration are determined. For the buckling analysis of the cylinders, a constant pressure of 1 Pa will be applied, the interference values are varied (for compound cylinders), the frictional coefficient values are varied from 0 to 0.65 (for compound cylinders), and the buckling pressure coefficients and mode shapes of vibration are determined. In this report, the simulations conducted with the Single Thin-Walled Cylinder show that the cylindrical structure generally stiffens under internal pressure and weakens under external pressure. The simulations conducted with the Compound Cylinder show that the presence of friction at the interface of the compound cylinder generally stiffens and makes the structure resistant towards deformation and presence of interference weakens the structure instead. iii Following the complete analysis of the data from the simulation, the report will be concluded with the general behavior of the cylindrical structure under specific influences, the methods that can be used to mitigate the effects of each of these influences and areas that future researches can target.